Relationship between the sense of coherence and quality of life among institutionalized elders in Bengaluru city India: A questionnaire study - B Kumara Raja; G Radha; R Rekha; S K Pallavi (Wolters Kluwer Medknow Publications, 2015)
Introduction: Aged people living in residential homes have a higher prevalence of depression and stress which cause oral health-related problems, contributing to excessive morbidity, than do those who live in communities. Aim: To find the relationship between senses of coherence (SOC) and quality of life (QoL) using Geriatric Oral Health Assessment Index (GOHAI) among elderly residents of old age homes in Bengaluru city, India. Materials and Methods: A cross-sectional study was conducted among elderly residents of Bengaluru city, India. Data were collected using a validated questionnaire which record demographic details, oral hygiene practices, and oral health habits. SOC and oral health-related QoL was measured using 13-item short version of the SOC scale and 12-item GOHAI scale. Chi-square test and Pearson's correlation coefficient test were used for statistical analysis. All variables showing significant association (P < 0.05) were entered into a regression model to identify predictors of low GOHAI and SOC. Results: A total of 376 elderly residents participated in the study and completed the questionnaire. Among them 150 (39.9%) were men and 226 (60.1%) were women. SOC was statistically significant with gender (P = 0.008), marital status (P = 0.003), dentition status (P = 0.000), smoking (P = 0.043), and alcohol consumption (P = 0.043). Age (P = 0.036), gender (P = 0.045), dentition status (P < 0.019), and smoking (P = 0.042) were found to be associated with GOHAI, there also exist a strong Pearson's correlation (r = 0.712) between SOC and GOHAI scores. Conclusions: A strong positive correlation was found between SOC and GOHAI scores indicating elder's with low SOC had low GOHAI scores and vice versa. The elders in residential homes were found to have more self-reported oral health-related functional problems, so dental health education must be focused on the special needs of the disabled, dependant and socio - economically deprived geriatric population to improve their QoL.